Indigenous Amazonians on air: Shipibo–Konibo radio broadcasters and their social influence in Peru. (June 2019) - Oyarce-Cruz, Jacqueline; Medina Paredes, Melissa; Maier, Markus
This article describes how Peruvian Shipibo–Konibo people instrumentalize local radio stations to participate in civil society and to become social leaders supported by their communities. The investigational group consisted of Shipibo–Konibo communicators, all of them are men, who work at local radio stations located in the region Ucayali, Amazonas, Peru. The indigenous radio broadcasters interviewed were chosen from the most popular radio stations of Ucayali. Topics in radio programs are politics, corruption, abuse, mishandling, as well as celebrations, traditional holidays, communities' anniversaries, and other cultural activities. Promoting social demands of their localities has given rise to new generations who now attend university and conduct radio programs in Shipibo–Konibo and Spanish, to communicate their concerns. It is an exploratory type research with a qualitative approach, focused on radio programs that got more local audience in the Peruvian Amazonia.